Fabrication and pseudocapacity behavior of elm flower branch-like nickel@graphene fibers1. Issue 39 (2nd May 2015) - Yu, Borong; He, Hui; Lin, Yongxing; Liu, Xianglan; Tian, Xingyou; Ding, Xin
<x xml:space="preserve">Abstract</x> A facile strategy is demonstrated to fabricate novel elm-flower-branch-like fibers on which nickel@graphene nanosheets are grown to form three-dimensional hierarchical architectures.